Synthesis of Silver Nanoparticles Doped in the Zeolite Framework - Kia Kojoori, Reza; Sadegh Samiei, Sepehr (Asian Journal of Chemistry, 2012)
In this article, synthesis of silver nanoparticles doped in the zeolite type A, at room temperature and in the absence of any additive reagents has been considered. This synthesized sample showed considerably antibacterial activity which was proved against gram-negative bacteria (i.e. Escherichia coli and Shigella dysentriae) and gram positive (i.e., Staphylococcus aureus and methicillin-resistant Staphyloccus aureus) by disk diffusion method using Mueller-Hinton agar at different sizes of silver nanoparticles.